2018
DOI: 10.1007/s40095-018-0270-z
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the surface and geometry of plate fin heat exchangers for increasing heat transfer rate

Abstract: This paper investigates the flow field and turbulent flow heat transfer around an array of plain and perforated fin using Fluent software within the range of 20,000-50,000 Reynolds. Regarding the turbulent flow, the k-ε RNG turbulence model was implemented, and SIMPLE algorithm was used for solving the equations of three-dimensional, steady, and incompressible flow. In the simulation process, air was considered as the working fluid with consistent physical properties. The results revealed that perforated fins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…Energies 2020, 13 In this section, stresses are calculated in the vertical direction for the plain fin brazed seam. Global stresses for the complete PFHE assembly are shown below in Figure 10.…”
Section: Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Energies 2020, 13 In this section, stresses are calculated in the vertical direction for the plain fin brazed seam. Global stresses for the complete PFHE assembly are shown below in Figure 10.…”
Section: Stressmentioning
confidence: 99%
“…They concluded that, under the same operating and geometrical conditions, the CVGPF channel showed the best thermal-hydraulic performance [12]. In another study, plain and perforated fins were analyzed, and it was concluded that, in perforated fins, increased heat transfer was observed with an overall pressure drop as compared to plain fin [13]. Recently, Peng et al [14] investigated the inlet design to PFHE on the basis of improved heat transfer; however, its effect on structure stability was not considered.…”
Section: Introductionmentioning
confidence: 97%
“…The results indicated that the elliptical tube showed better thermal performance and a 30%-40% increase in pressure drop than that of circular tubes. Shahdad et al [23] carried out studies on the heat transfer rate of plain and perforated plate-fin heat exchangers. It was revealed that perforated plate-fin has a higher heat transfer coefficient and Nusselt number than plain fin.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer rates, heat transfer performances, pressure drops, and system performances of different perforated fins were compared with solid fins of various geometries. Shahdad and Fazelpour 26 investigated the flow field and turbulent flow heat transfer around an array of plain and perforated fin using Fluent software within the range of 20,000–50,000 Reynolds. Regarding the turbulent flow, the k - ε RNG turbulence model was implemented, and the SIMPLE algorithm was used for solving the equations of three-dimensional, steady, and incompressible flow.…”
Section: Introductionmentioning
confidence: 99%